Developing RekonX-AR: An Interactive Augmented Reality Learning Media for Bank Reconciliation in Vocational Accounting Education - Aulia Zein Nur Arifah; Susanti (Journal of Educational Management Research, 2026)
This study aims to develop and evaluate the feasibility of RekonX-AR, an interactive learning media integrating Smart Apps Creator 3 and Assemblr Edu to facilitate students’ understanding of bank reconciliation. The development was motivated by the limited use of technology-integrated learning media and the complexity of bank reconciliation concepts, which require more interactive and contextual visualization to enhance conceptual understanding. This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The resulting product is an application-based learning medium integrated with Augmented Reality (AR), featuring learning materials, instructional videos, AR-based simulations, case studies, formative quizzes, and reflection activities. The findings indicate that RekonX-AR achieved a high level of feasibility, with material expert validation reaching 92% and media expert validation 98%, both categorized as Very Feasible. A limited trial involving Grade XI accounting students also demonstrated a positive response of 91%, classified as Very Good, indicating that the product is practical and well accepted by users. These findings imply that RekonX-AR can serve as an innovative technology-enhanced learning medium to support interactive learning, strengthen conceptual understanding, and improve students' learning engagement in accounting education.